The Mapping of English Action Verbs and their Indonesian Translation with Special Reference to Novel Divergent - Ni Made Made Muliani (Soshum: Jurnal Sosial dan Humaniora, 2019)
In translation, meaning and messages remain a priority that must be maintained and delivered in order for communication to proceed properly. In fact, translating a particular text is somewhat complicated, especially in translating a verb that has several different meanings. This study discussed the procedure of translation of verbs in English (source language) into the Indonesian language (target language), and how the verb is mapped into the Indonesian language. This research uses qualitative method, with Divergent novel data source in English compiled by Roth and its translation into Indonesian Divergent translated by Prameswari. The theory used in this research is the theory of Vinay and Darbelnet (in Venuti, 2000) about translation procedures that include borrowing, calque, literal translation, transposition, modulation, equivalence, and adaptation. And the theory of Wierzbicka (1996) which discusses the mapping.